A guide for interprofessional case presentations. (July 2014) - Gilbee, Alana; Baulch, Julie; Leech, Michelle; Levinson, Michele; Kiegaldie, Debra; Hood, Kerry
Summary Background Opportunities for interprofessional learning (IPL) and the promotion of interprofessional (IP) communication at the undergraduate level are important goals of health science faculties. IPL activities with shared curriculum validity to promote full student engagement can be challenging to identify. Case presentations that focus on patient‐centred learning are one type of activity that is likely to have clinical relevance to all undergraduate groups. Guiding students and facilitators on this approach using a structured framework is necessary to maximise the desired IPL outcomes. Context The framework was informed by two settings. Firstly, by a large metropolitan health service that provided IP clinical placements (ICPs). Six 2‐week placements in aged care rehabilitation were completed by medical, nursing and allied health students Secondly, by a an inner Melbourne private hospital where weekly IP case presentations were established. Innovation The innovation was a framework developed by clinical teachers and academics across two health services to guide facilitators and students participating in an IP case presentation. Implications This framework, highlighting both strategies for success and potential pitfalls, may provide a guide to teachers wishing to establish student IP case presentations within their health service or clinical placement context. The deployment and use of this framework may then provide a basis to evaluate IP case‐based presentations for formative or summative student assessment.